The water paradox : overcoming the global crisis in water management - Barbier, Edward, 1957- (Yale University Press, 2019)
A radical new approach to tackling the growing threat of water scarcity. Water is essential to life, yet humankind's relationship with water is complex. For millennia, we have perceived it as abundant and easily accessible. But water shortages are fast becoming a persistent reality for all nations, rich and poor. With demand outstripping supply, a global water crisis is imminent. In this trenchant critique of current water policies and practices, Edward Barbier argues that our water crisis is as much a failure of water management as it is a result of scarcity. Outdated governance structures and institutions, combined with continual underpricing, have perpetuated the overuse and undervaluation of water and disincentivized much-needed technological innovation. As a result "water grabbing" is on the rise, and cooperation to resolve these disputes is increasingly fraught. Barbier draws on evidence from countries across the globe to show the scale of the problem, and outlines the policy and management solutions needed to avert this crisis